SISTEM PENGHARGAAN DALAM MENINGKATKAN EFEKTIFITAS KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN KERINCI - pardinal, pardinal (LPPM STIA Nusantara Sakti, 2023)
Analysis of the Rewards System in Increasing Employee Work Effectiveness at the Kerinci Regency Ministry of Religion Office. For this reason, the research aims to explain whether the Reward System can increase the effectiveness of employee work at the Kerinci Regency Ministry of Religion Office, and the obstacles faced by the Kerinci Regency Ministry of Religion in implementing the reward system. The benefit of this research is to find out whether the reward system implemented can increase the work effectiveness of employees at the Kerinci Regency Ministry of Religion Office. The method used is Qualitative Inferman research is 5 people. The results of this research can be concluded. The Reward System for Improving Employee Work Effectiveness at the Kerinci Regency Ministry of Religion Office has been carried out in accordance with applicable regulations, although there is still not optimal training given regarding work duties after transfer of position, and bonuses in other forms such as certificates and gifts are only given to one to five employees at the Kerinci Regency Ministry of Religion Office. The awards received by employees at the Kerinci Regency Ministry of Religion Office can increase employee work effectiveness, this is proven by employees being able to complete work on time, the work results achieved are in accordance with the Tupoksi and SKP and the costs incurred in completing the work according to plan. The obstacles in implementing the Award System at the Ministry of Religion Office are 1. The budget for giving special awards to ASN cannot be budgeted, because the government already cares about all ASN of the Ministry of Religion, in the form of performance allowances as awards 2. There is no budget for awards at the Ministry of Religion, especially in the districts detailed, because every job has a duty and function.